Translational regulation during stage transitions in malaria parasites. (11th November 2014) - Cui, Liwang; Lindner, Scott; Miao, Jun
Abstract : The complicated life cycle of the malaria parasite involves a vertebrate host and a mosquito vector, and translational regulation plays a prominent role in orchestrating the developmental events in the two transition stages: gametocytes and sporozoites. Translational regulation is executed in both global and transcript‐specific manners. Plasmodium uses a conserved mechanism involving phosphorylation of eIF2α to repress global protein synthesis during the latent period of sporozoite development in the mosquito salivary glands. Transcript‐specific translational regulation is achieved by a network of RNA‐binding proteins (RBPs), among which the Dhh1 RNA helicase DOZI and Puf family RBPs are by far the best studied in Plasmodium . While the DOZI complex defines a new P granule with a role in protecting certain gametocyte mRNAs from degradation, the Puf proteins appear to repress expression of mRNAs in both gametocytes and sporozoites. These examples underscore the significance of translational regulation in Plasmodium development.